Perbandingan Konsep Hukum dalam Epistemologi Positivisme dan Materialisme - Fahrazi, Mahfud (Melayunesia Law, 2018)
The concept of law is the idea of the law which is used as the basis of a legal state to mobilize its laws. The concept of law is important because almost all countries use the law as a basis for mobilizing, bring order and prosperity of the country. There are two legal concepts, namely the concept of legal positivism and materialism. Both the concept of this law provides a very significant effect in most countries in the world. The concept of legal positivism emphasizes that the law should be freed from all the elements so that the law is an autonomous authority. The concept of law of materialism agitates that the law must be present in the upper structure and the basic structure. The law is present in the upper structure because the law emerges from ideology. The law is present in the basic structure because the law functions to regulate and simplify the production processes.